2019
DOI: 10.1016/j.jare.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Smart nanocarrier-based drug delivery systems for cancer therapy and toxicity studies: A review

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
427
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 788 publications
(433 citation statements)
references
References 299 publications
(299 reference statements)
4
427
0
2
Order By: Relevance
“…25,26 Actually, the nanocarrier is more preferable than traditional formulation in improving the efficacy of topical therapeutic, minimizing the side-effects of prolonged use and reducing dose of administration. 29 We developed a topical preparation based on liposomemediated transdermal delivery of miR-210 antisense to overcome the limitation of penetration skin barriers and improve the specific penetration without unwanted effects on skin. 29 We developed a topical preparation based on liposomemediated transdermal delivery of miR-210 antisense to overcome the limitation of penetration skin barriers and improve the specific penetration without unwanted effects on skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Actually, the nanocarrier is more preferable than traditional formulation in improving the efficacy of topical therapeutic, minimizing the side-effects of prolonged use and reducing dose of administration. 29 We developed a topical preparation based on liposomemediated transdermal delivery of miR-210 antisense to overcome the limitation of penetration skin barriers and improve the specific penetration without unwanted effects on skin. 29 We developed a topical preparation based on liposomemediated transdermal delivery of miR-210 antisense to overcome the limitation of penetration skin barriers and improve the specific penetration without unwanted effects on skin.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Liposome is one of the most reported nanocarriers, which is a naturally occurring phospholipid-based amphipathic nanocarrier. 29 We developed a topical preparation based on liposomemediated transdermal delivery of miR-210 antisense to overcome the limitation of penetration skin barriers and improve the specific penetration without unwanted effects on skin. Then, we applied this topical drug, NG-anti-miR-210, in the IMQ-induced psoriasis-like mouse model and confirmed that NG-anti-miR-210 exhibited equal therapeutic effect on psoriasis-like inflammation but was safer and more convenient compared with i.d.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, nanocarrier can be synthesized from polymers that are able to respond to specific stimuli based on physiochemical differences between cancer and non-cancerous cells, leading to the development of smart drug delivery systems [45]. Their aim is to reduce dosage frequency in a spatially controlled manner and facilitate the delivery and accumulation of the therapeutic system to the target tumor tissue.…”
Section: Nanocarriers For Gene Therapy and Smart Delivery Systemsmentioning
confidence: 99%
“…Their aim is to reduce dosage frequency in a spatially controlled manner and facilitate the delivery and accumulation of the therapeutic system to the target tumor tissue. Followed by the release of anticancer agent at the specific location at a precise concentration based on internal or external stimuli [45]. Smart polymer nanocarriers can respond to stimuli such as changes in pH, enzyme configurations, redox reactions and light [45].…”
Section: Nanocarriers For Gene Therapy and Smart Delivery Systemsmentioning
confidence: 99%
“…Using nanocarriersf or drug delivery has been considered to be effective in suppressing negative systematic side effects of the distributed drugs, while retaining their therapeutic effects. [6,7] Several nanocarriersb ased on variousm aterials have been reported in literature for delivery of ATO. These include polylactic acid/magnetic hybrid nanoparticles, polyacrylic acid cappedm esoporous silica nanoparticles (MSNs) and magnetite dopedm esoporous silica nanoparticles.…”
Section: Introductionmentioning
confidence: 99%